Development of Seeder Design and Technologies of Seed Tape Planting - M. E. Chaplygin; Yu. S. Tsench; A. V. Podzorov (Сельскохозяйственные машины и технологии)
This paper emphasizes the challenges associated with mechanizing and ensuring quality control in the process of sowing seeds using seed tapes (seed ropes). Each examined invention integrates design and technological solutions developed to improve efficiency and effectiveness. (Research purpose) The study aims to examine the development and evolution of aggregated seed tape planters; focusing on their structural features; and component base. (Materials and methods) The study employs a historical-analytical approach drawing on publications from scientific print sources; patent documents from databases such as Espacenet; the Federal Institute of Industrial Property; the Database of Patents of the USSR; and photographic materials. (Results and discussion) The study provides information on the development of the first devices designed for seed tape sowing. It identifies typical design solutions for seed tape sowing technology across different countries. (Conclusions) A review of existing inventions has been conducted; leading to the identification of several promising design and technological solutions for the development of new machines in this category. Specifically; the study highlights the employment of tape-guiding elements that reduce tape breakage and seed damage; as well as tape break detection and tension control systems. It also emphasizes the versatility of the tape-guiding system; which accommodates tapes of different types and sizes. Additionally; the study highlights the incorporation of soil-cultivating units; a disc-anchor coulter for creating an even and compacted seed bed for the seed tape; and a localized irrigation system to accelerate seed germination and facilitate the biodegradation of the tape carrier.